2015
DOI: 10.1097/hp.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Applicability of FISH-based Prematurely Condensed Dicentric Chromosome Assay in Triage Biodosimetry

Abstract: The dicentric chromosome assay (DCA) has been regarded as the gold standard of radiation biodosimetry. The assay, however, requires a 2-d peripheral blood lymphocyte culture before starting metaphase chromosome analyses to estimate biological doses. Other biological assays also have drawbacks with respect to the time needed to obtain dose estimates for rapid decision on the correct line of medical treatment. Therefore, alternative technologies that suit requirements for triage biodosimetry are needed. Radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Earlier reports demonstrated that variability could influence the results of PCC assays and this should be taken into account while planning the experiments. It was shown that the initial yield of PCC fragments soon after irradiation was high, but drop quickly even at 3 h postirradiation and reached plateau at 6–8 h and stayed stable up to 48 h.[ 7 8 ] The rejoining kinetics of excess PCC fragments were highlighted in earlier publications[ 4 9 10 ] and suggested that PCC assay is sensitive to the delay time between exposure and analysis. Therefore, experimental investigation should be performed in more realistic condition to the accident situation taking into account the kinetics of PCC fragments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier reports demonstrated that variability could influence the results of PCC assays and this should be taken into account while planning the experiments. It was shown that the initial yield of PCC fragments soon after irradiation was high, but drop quickly even at 3 h postirradiation and reached plateau at 6–8 h and stayed stable up to 48 h.[ 7 8 ] The rejoining kinetics of excess PCC fragments were highlighted in earlier publications[ 4 9 10 ] and suggested that PCC assay is sensitive to the delay time between exposure and analysis. Therefore, experimental investigation should be performed in more realistic condition to the accident situation taking into account the kinetics of PCC fragments.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent years, PCC method has attracted much attention in laboratories because of its potential use in biological dosimetry. Several modifications of this method such as analysis of PCC-ring fragments,[ 8 9 ] analysis PCC-dicentric chromosomes using peptide nucleic acid centromere and telomere probes[ 10 11 ] were recently introduced into practice, and such improvements have increased the capability of this technique in estimating the dose more precisely. Therefore, the introduction of PCC fusion assay as a platform for other PCC-based techniques is the first step toward further strengthening of the biodosimetry laboratories worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the development of centromeric/telomeric (C/T) peptide nucleic acid (PNA) probes and their simultaneous use in lymphocyte PCCs in combination with FISH, has offered a new dynamic to the PCC-method, enabling the analysis of dicentrics and centric ring chromosomes directly in non-stimulated lymphocytes, with a level of accuracy and ease not possible previously [20][21][22]. In the present work, we make use of the PCC-method in combination with PNA probes and the FISH technique in order to construct a dose response curve for up to 10 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, Pantelias et al [34] used the centromeric heterochromatin banding technique (C-banding) for analyzing the frequency of IR induced dicentric chromosomes. Subsequently, the fluorescence in situ hybridization (FISH) technique was employed using DNA probes specific for human centromeres and telomeres for DC detection in PCCs obtained from non-stimulated lymphocytes [3537]. Karachristou et al [35] demonstrated the utility of PCC-FISH technique for triage biodosimetry by constructing a dose response curve up to 10Gy of γ-rays.…”
Section: Introductionmentioning
confidence: 99%